STUDENTS’ PERCEPTION OF USING GOOGLE LENS AND TRADITIONAL PRINTED DICTIONARY IN VOCABULARY LEARNING - Syahrul Alqi Fariq; Syarifah Farahdiba; Maemuna Muhayyang (JTechLP: Journal of Technology in Language Pedagogy, 2026)
This research aims to analyze and compare students’ perceptions of using Google Lens and traditional dictionaries in English vocabulary learning. This research uses a quantitative approach with a descriptive comparative design. The participants were 39 students of Universitas Negeri Makassar selected through purposive sampling. The instrument used was a Likert-scale questionnaire measuring perceived ease of use, perceived usefulness, and learning engagement. The data were analyzed using descriptive statistics and comparative analysis with SPSS. The findings reveal a statistically significant difference between students’ perceptions of Google Lens and traditional printed dictionaries, with a significance value of 0.000 < 0.05. Students demonstrated more positive perceptions toward Google Lens in terms of practicality, efficiency, and engagement. Therefore, it can be concluded that Google Lens is perceived as a more effective and acceptable medium for vocabulary learning in the digital era.